Gamification to Increase User Interaction - Loureiro, Guilherme da Silva Martins (2022)
Companies across the world use multiple ways and frameworks that try to lead their employees to feel more motivated and productive on work hours. Nowadays, with the increase success stories within the concept of gamification, it has been a great push for most international companies to look at said gamified solutions as an alternative to solve most of the issues found within the workplace. With that in mind, the main objective of this project will be to answer to an identified user interaction problem within Hitachi Solution’s employee’s hub, through the use of gamification. Throughout this thesis process, with the help of the framework Design Science Research Methodology (DSRM), there has been identified and demonstrated all aspects surrounding the problem, the design, the development and the evaluation metrics to assert the success of said solution. Initially, an analysis of gamification is done so to understand what drives people to use and interact with this type of systems. After, many frameworks are put on show and compared to each other so to better understand the pros and cons of the different methods. Lastly, there is a display of success cases where this type of solutions are currently massively adopted. Later on, many solutions are created based on the innovation process and then put to the test based on their value to this thesis. With that in mind, the solution chosen on the previous step, got to be designed and implemented on Hitachi’s system. This implementation was based on a agile methodology with recurrent scrum meetings at the end of short sprints (2 week sprints) and developed mainly in JavaScript, with the help of the Veu framework. As a last step, the gamification was deployed to the production environment where it got to be used/tested as a pilot version of the system. Posterior to this, some of the users underwent a semi-structured interview with the objective of gathering feedback and understand their feelings towards the new features. Concluding, after the tests were done, these were analysed and a slight improvement on interaction was observed. These findings allowed the business to green light further development on the project so to be able to increase even further the interaction level.